Accountability in Healthcare in India - Manish Priyadarshi; Sanjiv Kumar (Wolters Kluwer Medknow Publications, 2020)
Today, health is a human right in India, and the government is working hard for universalization of health services provision till the grassroots. Health without accountability is a challenging task in hand, and recently, state governments drafted a bill toward public health system to move in the strengthened direction of accountability mechanism. Accountability is the quality or state of being accountable, and it is an important component of the health-care reforms in India. This article provides more nuanced understanding of accountability which includes the specification of accountability, conceptual framework of accountability, and its potential approaches for how accountability is viewed today in India with reference to the Central, State, District, and other stakeholders. It examines the role of accountability in making accountable health plans, and its relationship governance/ownership structures as a key component of health-care reforms as improved accountability is a major element in improving the health system performance. The article elaborates on the definition of accountability in terms of answerability and sanctions and distinguishes the three types of accountability, namely financial, performance, and political/democratic. The article describes three accountability-enhancing strategies, namely reducing the pilferage, assuring acquiescence with procedures and standards, and improved learning from the past experience. The recent events in Indian health care put forward a serious issue on how accountability can be fixed if health mishaps happened and how we can make our health plans accountable to the needs and aspiration for the people of India. Overall, the accountability is discouraging and more needs to be done to enhance the accountability compliance in India.